Storytelling Method in Increasing Language Proficiency: Speaking, Vocabulary, and Understanding - Ika Nuriyanti (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2025)
The purpose of this study is to present comprehensive research on enhancing four English language proficiency as integrated abilities at SMP Islam Hasanuddin Malang grade 1, with the aid of storytelling. 1) The process of enhancing four English language proficiency levels as an integrated skill with the help of storytelling, and 2) The outcomes of this process are included in this study. Action research, the research methodology employed, uses instruction that is thought to be able to enhance the learning process, which is likely to enhance the outcomes that students attain. According to the study, storytelling is a useful method for teaching English. When the teacher interferes too much with the students' actions, the story-telling process will not go well. In order to have many opportunities to communicate in English, students must work independently to become self-sufficient and autonomous learners. The use of stories to provide information in an interesting way and increase student involvement makes storytelling a successful language learning strategy.